Spectator isobar production in the A([gamma], [nu]NN)BA([gamma], [nu]NN)B reaction; International Journal of Modern Physics E; Vol. 27, iss. 5 - Glavanakov I. V. Igor Vladimirovich (2018, 2018)
Title screen